Contract farming and access to formal credit in South Africa: A case of small-scale sugarcane growers in the Felixton Mill area of KwaZulu-Natal - Machethe, Charles Lepepeule (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2019.